The development of interlanguage pragmatics in L2 Arabic: The production of apology strategies. (June 2018) - Al Masaeed, Khaled; Waugh, Linda R.; Burns, Katharine E.
Abstract: This study investigated apology strategies in formal and informal situations of American university students learning Arabic as a foreign language (AFL) in the United States. Data were collected from spoken discourse completion tasks for 15 Arabic native speakers and 45 university students from three different proficiency levels. The findings show that there is a positive relationship between an increase in proficiency level and the production of apology strategies as well as between level of proficiency and approximation of native speakers' (NSs) apology strategy production norms. Learners in general used more statements of regret than the NS group did. Unlike what previous studies posit, the findings show that lower proficiency learners have the tendency to produce more explicit apologies than those at a higher proficiency. Results also demonstrate that verbosity was salient in oral production, which is at odds with previous claims that it tends to occur only in learners' written responses. In addition, findings show that the NS group tends to provide vague explanations when offering apologies, whereas the learners prefer to provide specific reasons for their offense. The study also discusses pedagogical implications for teaching apologies in L2 Arabic.